School Mediation as a Means of Preventing Social Maladjustment of Students from Risk Groups - Belkina-Kovalchuk, Olena V.; Durmanenko, Evgeniya A.; Martyniuk, Tetyana A.; Petruk, Victoria V.; Cherneta, Svitlana Yu. (Journal of Intellectual Disability - Diagnosis and Treatment, 2021)
This research study examines issues related to the prevention of social maladjustment of students from risk groups through the use of school mediation. The relevance of the stated research topic is due to the significant scale of the spread of juvenile delinquency in modern Ukrainian society and the growing popularity of school mediation to resolve and prevent emerging social problems at the school stage. This research study aims to identify and state the main aspects in the impact of the practice of school mediation on the factors that are fundamental in the social adaptation of students from the risk group in the modern realities of Ukrainian society. The leading approach in this scientific research is a combination of analytical and logical methods of researching the issues presented as the main ones in this work. The main results of this research study were: identifying the degree of the positive impact of mediation practice at school on the students’ consciousness in the context of the need for their subsequent social adaptation and stating the fact that this practice is promising in the future to resolve issues of social fitness specifically for students from risk groups in modern social conditions. The applied value of this research work is identifying the prospects for further research of a complex of factors affecting the social situation in Ukraine in the context of the subsequent spread in a society of groups that pose a social danger, and the possibilities of school mediation as a means of preventing the development of such a phenomenon already in the early stages. Subsequent scientific research on the role of school mediation in the context of preventing the development of juvenile delinquency and assessing its effectiveness in preventing the social spread of students at risk will help supplement the existing information picture of research in this area and will become the starting point for an objective analysis of the need to use school mediation as means of preventing the spread of juvenile delinquency in Ukraine.